2006
DOI: 10.1002/mrc.1802
|View full text |Cite
|
Sign up to set email alerts
|

Structure elucidation of a new friedelane triterpene from the mangrove plant Hibiscus tiliaceus

Abstract: From the stem and bark of the mangrove plant Hibiscus tiliaceus, a new friedelane-type triterpene named 27-oic-3-oxo-28-friedelanoic acid (1) together with eight known triterpenoids involving five friedelane-type derivatives was isolated. The structure of 1 was determined by extensive 2D NMR (DQF-COSY, HMQC, HMBC, and NOESY) data analyses. All the compounds were obtained from mangrove plants for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 11 publications
0
10
0
2
Order By: Relevance
“…H. tiliaceus L. (Malvaceae) is used in folk medicine for treating fevers, to soothe coughs, dysentery, and ear infections. A primary chemical examination of this plant indicated that the main components were oleane-type triterpenes, with these co-occurring with the friedelin-type (Li et al 2006). An examination of the fermentation broth of the Phomopsis sp.…”
Section: Mangrove Endophytic Fungimentioning
confidence: 99%
“…H. tiliaceus L. (Malvaceae) is used in folk medicine for treating fevers, to soothe coughs, dysentery, and ear infections. A primary chemical examination of this plant indicated that the main components were oleane-type triterpenes, with these co-occurring with the friedelin-type (Li et al 2006). An examination of the fermentation broth of the Phomopsis sp.…”
Section: Mangrove Endophytic Fungimentioning
confidence: 99%
“…In China, this species is mainly distributed along the southern and southeastern coastlines [1]. This plant is used as traditional medicine in Asia and Africa to treat diseases such as fever, cough, phlegm, and dysentery [2]. Previous investigations centered on H. tiliaceus led to the isolation of a series of oleanane-and friedelane-type triterpenoids [2].…”
mentioning
confidence: 99%
“…To the best of our knowledge, the present investigation represents the first isolation of this type of compounds from mangrove plants. The isolation of compounds 1 -3 represents a new addition to the molecular diversity of Hibiscus tiliaceus, compared with other types of triterpenoids isolated from the same species [2].…”
mentioning
confidence: 99%
See 2 more Smart Citations